Speech Lab in a Box: A Mandarin Speech Toolbox to Jumpstart Speech Related Research - Chang, Eric; Shi, Yu; Zhouo, Jianlai; Huang, Chao (EuroSpeech 2001, 2001)
The necessity of gathering data has been an impediment for researchers and students who are interested in getting started in the fields related to speech recognition. We are proposing a new approach of distributing data that is designed to quickly help researchers and students achieve a set of baseline results to build upon. Furthermore, by leveraging publicly available programs, all researchers will be able to exactly reproduce results that are described in this paper. We also aim to facilitate comparison of recognition results in the field of Mandarin speech recognition by including a testing set in the toolbox. We describe a toolbox that includes Mandarin speech data from 125 speakers, suitable language model, scripts and data files required for recreating a set of baseline experiments, and a copy of Microsoft SAPI 5.0 SDK that can help professors and students who wish to jumpstart research programs in speech technologies. By lowering the barrier of entry to the field, we hope to encourage more participation in the study of Mandarin speech recognition.